PENGARUH FASILITAS DAN HARGA TERHADAP MINAT BELI ULANG KONSUMEN PADA UMKM U MUDA DIYUB BAK MEE DI KECAMATAN KOTA JUANG KABUPATEN BIREUEN - Fauziani, Dinda; Firmansyah, Denny (IndOmera, 2025)
The development of Micro, Small, and Medium Enterprises (MSMEs) plays an important role in supporting local economic growth; however, increasing competition requires business owners to pay close attention to factors that influence consumers’ repurchase intention. This condition is observed at UMKM U Muda Diyub Bak Mee in Kota Juang Subdistrict, Bireuen Regency, where issues related to business facilities and pricing strategies have emerged. Therefore, this study aims to analyze the influence of facilities and price on consumers’ repurchase intention. This research employs a quantitative approach using a survey method by distributing questionnaires to 289 respondents. The data were analyzed using multiple linear regression analysis. The results indicate that facilities and price have a positive and significant effect on repurchase intention, both partially and simultaneously. The regression model obtained is Y = 0.631 + 0.422X₁ + 0.378X₂, with an R Square value of 0.597. These findings demonstrate that facilities have a more dominant influence than price on consumers’ repurchase intention at UMKM U Muda Diyub Bak Mee.